Characterizing Community Structure of Benthic Infauna From the Continental Slope of the Southern California Bight - Gillett, David J.; Gilbane, Lisa; Schiff, Kenneth C. (Frontiers in Marine Science, 2021)
Infauna are an ecologically important component of marine benthic ecosystems and are the most common faunal assemblage used to assess habitat quality. Compared to the shallower waters of the continental shelf, less is known about the benthic fauna from the continental slope, especially how the communities are structured by natural gradients and anthropogenic stressors. The present study was conceived to rectify these data gaps and characterize the natural, baseline structure of the benthic infauna of the upper continental slope (200-100m) of the Southern California Bight. We aggregated benthic infauna, sediment composition, and sediment chemistry data from different surveys across the Southern California Bight region (750 samples from 347 sites) collected between 1972 and 2016. We defined 208 samples to be in reference condition based upon sediment chemistry and proximity to known anthropogenic disturbances. Cluster analysis of the reference samples was used to identify distinct assemblages and the abiotic characteristics associated with each cluster were then used to define habitat characteristics for each assemblage. Three habitats were identified, delineated by geography, depth, and sediment composition. Across the habitats, there were detectable changes in community composition of the non-disturbed fauna through time. However, the uniqueness of the habitats was persistent, as the fauna from each habitat remained taxonomically distinct from irrespective of the decade of their collection. Within each habitat, subtle, assemblage-scale responses to disturbance could be detected, but no consistent patterns could be identified among the component taxa. As with the non-disturbed samples, there were compositional changes in the fauna of the disturbed samples through time. Despite the changes, fauna from disturbed and non-disturbed samples remained taxonomically distinct from each other within each decade of the dataset. After considering both the spatial and temporal patterns in the fauna of slope ecosystem, it became apparent that there was a high degree of stochasticity in the taxonomic organization of all three habitats. This would suggest that the benthic fauna from these communities may be neutrally organized, which in turn poses interesting challenges for future development of condition assessment tools based upon the benthic fauna in these habitats.